EXPRESSION AND CELL LOCALIZATION OF CHOLECYSTOKININ IN THE GUT OF WHITESEA BREAM (DIPLODUS SARGUS) AFTER FEEDING AND FASTING - GUERRERA, Maria Cristina; LEVANTI, Maria; GERMANA', Antonino; MUGLIA, Ugo; V. Micale (2012)
Introduction The peptide hormone cholecystokinin (CCK), a member from the gastrin-CCK family, has a widespread distribution within the gastro-intestinal tract (GIT), as well as the central and peripheral nervous system in vertebrate. The CCK is secreted by the midgut and plays a key role in digestive physiology of vertebrates including teleosts, by stimulating pancreatic secretion, gut motility, and gallbladder contraction, as well as by delaying gastric emptying (1). Moreover, CCK is involved in the regulation of food intake and satiation and recently has been demonstrated the occurrence and localization of CCK in a saltwater teleost Diplodus puntazzo (2). Nevertheless, secretion of CCK by the hindgut is controversial, and its biological activity remains to be elucidated. The present paper addresses the regional distribution of intestinal CCK in the white sea bream, Diplodus sargus, as well as the possible involvement of hindgut CCK in digestive processes. Materials and methods White sea bream, Diplodus sargus L, were reared at the C.I.S.S. (Experimental Ichthyopathology Centre of Sicily, Veterinary Faculty, University of Messina, Italy) in 300 l indoor tanks. The regional distribution of CCKIR cells, CCK mRNA expression, and CCK protein expression in the gut, before and after starvation, was evaluated by immunohistochemistry, quantitative real-time RT-PCR (qPCR) and semi-quantitative Western blot, respectively. Results All examined samples from both fed and fasted fish displayed CCK immunoreactive cells (CCK-ir) in each considered segment. CCK-ir cells were mainly concentrated in pyloric caeca, and gradually decreased along the midgut and hindgut. RT-PCR analysis shows that fasting induced a significant decrease in CCK-2 in all intestinal segments, and a significant increase in CCK-1 in pyloric caeca, anterior and posterior midgut. On the other hand, no significant difference was induced by fasting on hindgut CCK-1. Semi-quantitative Western blot analysis shows that fasting induces a pronounced decrease in CCK ...